The Impact of Human Resource Development and Organizational Culture on The Quality of Public Service - Rachman, Ellys (Cendekiawan Indonesia Timur, 2024)
Public organizations stand as vital conduits through which government services are delivered to communities, aiming to significantly improve their well-being and welfare. This study adopts a qualitative research framework, specifically leveraging a descriptive methodology to explore the functioning of the Education and Training Personnel Agency along with the Civil Registry Office in Gorontalo City. By focusing on these entities, the investigation delves into the broader population of public service institutions in the city. A mix of data collection techniques, including interviews, questionnaires, and the review of pertinent documents, was utilized to gather insights. The findings reveal a pronounced influence of human resource development on the quality of public services in Gorontalo City, suggesting that investments in education and training of personnel are likely to yield improvements in service quality.Additionally, the study highlights the significant role of organizational culture in shaping the quality of public services, indicating that a positive corporate culture is instrumental in enhancing public service delivery. Together, these insights underscore the critical interplay between human resource development and organizational culture in elevating the standard of public services in Gorontalo City.